EFEKTIFITAS MODEL PEMBELAJARAN SOMATIC AUDITORY VISUALIZATION INTELLECTUALLY (SAVI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 33 KABUPATEN TEBO - Ngadimin, S.Pd (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to describe mathematical problem solving skills using the Somatic Auditory Visualization Intellectually (SAVI) learning model. The research uses a quantitative approach with experimental methods. The population in this study were seventh grade students of SMP Negeri 33 Tebo Regency. Sampling using simple random sampling technique. The selected sample is class VIIA as the experimental class and class VIIB as the control class. Collecting data through tests in the form of essay questions with five questions on the tube and cone material. The data analysis technique used to test the hypothesis is the independent sample t-test. From the analysis of the final test data in the experimental class obtained an average of 39.69 while the control class obtained an average of 26.64. Analysis using independent sample t-test is known that the value of t_ hitung = 3.0997 and t_table = 1.669. Because t_hitung > t_table then H0 is rejected and H1 is accepted. The conclusion of this study is that the understanding of mathematical concepts using the Somatic Auditory Visualization Intellectually (SAVI) learning model is better than conventional learning.